2010
DOI: 10.5572/ajae.2010.4.3.115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Individual Atmospheric Aerosols Using Quantitative Energy Dispersive-Electron Probe X-ray Microanalysis: A Review

Abstract: Great concerns about atmospheric aerosols are attributed to their multiple roles to atmospheric processes. For example, atmospheric aerosols influence global climate, directly by scattering or absorbing solar radiations and indirectly by serving as cloud condensation nuclei. They also have a significant impact on human health and visibility. Many of these effects depend on the size and composition of atmospheric aerosols, and thus detailed information on the physicochemical properties and the distribution of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 95 publications
(139 reference statements)
0
7
0
Order By: Relevance
“…Fe might be origin from the steel dusts which were produced as numerous train wheels roll through the subway tunnels. Several earlier studies (Kim and Ro, 2010;Lorenzo et al, 2006;Okinaga et al, 2000) indicated that Fe was a major source of pollution in one of the world's most extensive commuter rail systems. And Mori et al (2007) reported that the thermal metamorphism of train wheels gene- CaO, FeO, etc.…”
Section: Elemental Concentration Of Semi-bulkmentioning
confidence: 98%
“…Fe might be origin from the steel dusts which were produced as numerous train wheels roll through the subway tunnels. Several earlier studies (Kim and Ro, 2010;Lorenzo et al, 2006;Okinaga et al, 2000) indicated that Fe was a major source of pollution in one of the world's most extensive commuter rail systems. And Mori et al (2007) reported that the thermal metamorphism of train wheels gene- CaO, FeO, etc.…”
Section: Elemental Concentration Of Semi-bulkmentioning
confidence: 98%
“…This single-particle analytical technique, which is based on scanning electron microscopy (SEM) coupled with an ultra-thin window energy-dispersive X-ray spectrometer (EDX), can not only simultaneously detect the morphology and constituent elements of a single particle, but also provide transformation information on many environmentallyimportant particles of micrometer size, such as nitrates, sulfates, oxides or mixtures, including carbon matrices (Kim and Ro, 2010;Choel et al, 2005;Geng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In general, natural soil particles result from weathering and eroding of crustal rocks, and the major constituents of soil are similar to those of rock-forming minerals. The most common minerals constituting earth's crust are silicates.…”
Section: 14mentioning
confidence: 99%
“…Because low-Z particle EPMA can clearly identify carbonate, sulfate, and nitrate particles, it has been proven to be useful for the characterization of diverse environmental aerosol samples. [18][19][20][21][22] The combined application of these two techniques for the characterization of river sediments polluted with heavy metals has been reported to be quite successful. [23][24][25] In this work, soils collected at MSW-contaminated and apparently noncontaminated countryside sites were investigated using these two nondestructive techniques for the detailed characterization of their inorganic chemical compositions.…”
Section: Introductionmentioning
confidence: 99%